Istoría tu archaíu kósmu apó tus proïstorikús politismús tēs Anatolḗs éōs tēn epochḗ tu Iustinianú : a' táxē Eniaíu Lykeíu (Genikḗs paideías) - Mastrapá, Antṓnē N. (ITYE, Instituto Technologias Ypologistōn kai Ekdoseōn Diophantos, 2012)
This book is the result of trying to create a versatile and pedagogically suitable device that meets the needs of modern teaching of the course of history in the first grade of Lyceum.